(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper endeavors to examine and evaluate the evolving dimensions of Indo-US foreign policy, while also advocating for India’s significant role in international politics during the tenure of Prime Minister Narendra Modi. Since 2014, following his official designation, Modi has ardently pursued the transformation of India’s inquiries into becoming a distinguished global leader, characterized by adaptability and significant proactive initiatives. The reform of Indian foreign policy, following Nehru, is fundamentally rooted in a modified doctrine aimed at positioning India’s foreign policy as exemplary. The concept of ‘political capital’ represents a novel framework that seeks to connect with other domains. Essential Terms: foreign nations under the leadership of Narendra Modi. In a similar vein, the closeness between India and the United States is of the highest caliber. International relations, geopolitical dynamics, India-United States interactions, Prime Minister Narendra Modi, diplomatic efforts, strategic alliances. examine and emphasize the diverse interpretations regarding their diplomatic interactions. Since the inception of Modi’s administration, ongoing contemplation regarding Indo-US connectivity has significantly depended on Modi’s diplomatic approach in relation to the Obama and Trump administrations. In the progression of the novel. The engineering of foreign policy involving the superpower USA may lead India to become more effective following this approach. Several emerging trends are proving to be more effective in strengthening the strategic partnership between India and the United States. It is evident that the emerging multi-dimensional framework and institutional collaboration within the Indo-US partnership highlight recent developments that suggest a unilateral alignment in strategic partnership. Within the realm of the political engagement between the USA and India, we advance collectively, enhancing strategic ties, embarking on a journey of digital transformation, and formalizing a significant defense partnership. The 2+2 dialogue initiatives, the pursuit of prosperity through collaboration, and the grand events of Howdy Modi and Namaste Trump represent avenues for envisioning a new strategic pathway between the world’s largest and oldest democracies. Nonetheless, the previous decade of India’s civil nuclear agreement with the United States has significantly elevated the potential for strengthened and assured connections between the two nations. Indo-US partnerships in the protracted endeavour. However, Modi’s comprehension of power and interests regarding. The account of bilateral and multilateral agreements with US counterparts highlights the evolving dynamics. The perspective on India’s foreign policy. This paper endeavours to analyze the trajectory of Indo-USA relations and its implications for the international environment.